(untitled) (AYUSHDHARA, 2022)
The bulk of skin conditions are seen in Ayurveda as being within the category of Kushtha, or "Ayurvedic dermatology." It is listed as among the “Ashta Mahagada”. Eczema is the most prevalent skin condition with societal repercussions. Up to 20% of children and up to 3% of adults might have eczema, and existing data reveal that it is becoming more common, especially in developing nations. The clinical picture of eczema resembles with Vicharchika – a variant of Kshudra Kustha that Ayurvedic dermatologists frequently meet and is marked by the symptoms of Kandu (itching), Srava (discharge), Pidaka (vesicles), and Shyava varna (discoloration). Aim: to assess how Samshodhana and Samshamana Karma contribute to the treatment of Vicharchika w.s.r. to eczema. Material & Method: A 66 years old male patient came to NIA OPD no 25 on 06/04/2022 with complaints of Atikandu (severe itching with thick edematous skin) on forearms, forehead and anterior to neck region having cracks with discharge for 5 years. He took contemporary medicines for the problem but did not get significant relief. Intervention: We started Aragvadha Patra lepa and Panchtikta Ghrit Pana followed by Virechana Karma by giving Trivrita Avaleha. Marked relief was found in sign & symptoms within 7 days and cured within 21 days of treatment. Conclusion: Study concluded that the above Ayurvedic treatment can prove to be an effective alternate management in eczema with proper diet and regimen.